The Influence of Code of Ethics, Organizational Culture and Welfare on the Integrity of Supermarket Employees in Langsa, East Aceh - Usman, Hasanuddin; B, Mesra (International Journal of Social Science, Education, Communication and Economics, 2024)
This research was conducted to examine the influence of the Code of Ethics, Organizational Culture and Welfare on the Integrity of Supermarket Employees in Langsa, East Aceh. This research uses quantitative as the type of research and primary data as the source of research data. The way to collect data from this research is to distribute questionnaires to respondents. This research was conducted at Langsa Supermarket, East Aceh. The population of this research was 100 respondents and the sample used was the entire population. make a sample and use a saturated sampling technique, this research uses the SPSS measuring tool and the method used is multiple linear regression. The results of this research are as follows: The Code of Ethics has a positive and significant effect on Employee Integrity with a value of 0.275 with a significance of 0.001 < 0.05. Organizational Culture has a positive and significant effect on Employee Integrity with a value of 0.863 with a significance of 0.000. Sejahtera has a positive and significant effect on Employee Integrity with a value of 0.227 and a significant 0.004. Code of Ethics, Organizational Culture, Prosperity has a positive and significant effect together on Employee Integrity with a value of 30.209 and a significant 0.000.